Tinjauan Kriminologis Meningkatknya Kekerasan terhadap Anak di Wilayah Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak Kota Jambi - Mhd. Badri; Sumaidi Sumaidi; Reza Iswanto (Universitas Batanghari Jambi, 2025)
The rise in cases of violence against children in Jambi City is a concerning issue, deeply rooted in family dysfunction, economic pressure, and poor parenting. This phenomenon demands serious attention and comprehensive efforts involving firm law enforcement, strengthening family resilience through various support programs, increasing public awareness through ongoing education, and implementing effective early intervention. This study seeks to delve deeper into the root causes of this violence, identify the most relevant countermeasures, and analyze the various obstacles that hinder response efforts. By utilizing primary and secondary data, and applying in-depth qualitative analysis methods at the Jambi City Women and Children Protection Office, this study is expected to provide constructive recommendations to protect children from all forms of violence. The results indicate that the increase in violence against children in Jambi City is caused by economic, environmental, cultural, and educational factors. Preventive efforts include vitamin programs, outreach, and law enforcement, but obstacles such as family shame and a lack of resources remain.